Pengaruh Kedisiplinan, Kecerdasan Emosional Dan Komunikasi Terhadap Kinerja Pegawai Balai Desa Wiladeg Gunungkidul - Kurnia, Wais Al (Universitas PGRI Yogyakarta, 2020)
This study aims to know the effect of discipline, emotional intelligence and communication to employee performance. This study uses primary data by distributing questionnaires. The population of this study was all 35 employees of the Wiladeg Gunungkidul Village Hall. Data analysis method used multiple regression analysis, validity test, reliability, hypothesis testing (T test and F test) and test the coefficient of determination. The result of this study concluded that based on regression analysis obtained the following equation Y = Â 0,123 + 0,120X1 + 0,066X2 + 0,364X3 + e. Based on the hypothesis testing, the F test is known that joinly (simultaneously) variable discipline, emotional intelligence and communication significant effect on employee performance. The result of the t test (partial testing), variable discipline, emotional intelligenceÂ and communication has significant positive effect on employee performance.